2013
DOI: 10.1542/peds.2012-3462
|View full text |Cite
|
Sign up to set email alerts
|

Texting While Driving and Other Risky Motor Vehicle Behaviors Among US High School Students

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Distracted driving due to texting while driving (TWD) has emerged as an important teenage safety issue. Previous studies have shown that the self-reported prevalence of TWD among teenagers varies widely. WHAT THIS STUDY ADDS:In 2011, 45% of US high school students aged $16 years reported TWD during the past 30 days. TWD was positively associated with other risky motor vehicle behaviors; this association strengthened as frequency of TWD increased. abstract OBJECTIVE: To assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 32 publications
7
74
3
Order By: Relevance
“…Recently, Olsen et al (2013) found a relationship between frequent texting and other risky behaviors among high school students. A large literature has established that men engage in more risky behaviors than women, including speeding, running stop lights, and not wearing seatbelts (Cross et al, 2011;Harris et al, 2006).…”
Section: Personality Traits Of Risky Behavior and Impulsivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Olsen et al (2013) found a relationship between frequent texting and other risky behaviors among high school students. A large literature has established that men engage in more risky behaviors than women, including speeding, running stop lights, and not wearing seatbelts (Cross et al, 2011;Harris et al, 2006).…”
Section: Personality Traits Of Risky Behavior and Impulsivitymentioning
confidence: 99%
“…The rate reached 50% for young drivers age 18-24. CDC data for high school students for 2011 revealed that 44.5% had engaged in texting while driving (Olsen et al, 2013). Texting while driving is almost universal among college-age samples.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous epidemiologic studies of mobile device use have used methods such as retrospective selfreport or review of cell phone records to assess frequency of use. [11][12][13][14][15] However, simply measuring the frequency of device use fails to capture modes of use that are most relevant to parentchild interactions and thus may be insufficient to describe the true impact of this technology on child health and development. A relevant categorization framework is necessary to begin to study how mobile device use affects caregiver-child interaction.…”
mentioning
confidence: 99%
“…Seizure control, associated physical disorders, and intellectual ability, as well as risk-taking behaviors influence the discussion on driving at the time of transition or transfer. 1,2 A young person with epilepsy needs to achieve seizure control for a long enough period to be legally allowed to prepare for a driving test and obtain a license. In the epilepsy transition/transfer clinic setting, the physician needs to consider medical aspects, information provision, driving eligibility, as well as make a preliminary assessment of driving ability for those with additional impairment (Table 1).…”
Section: Drivingmentioning
confidence: 99%